Broad-band dielectric response of 0.5Ba(Ti0.8Zr0.2)O3–0.5(Ba0.7Ca0.3)TiO3 piezoceramics: soft and central mode behaviour. (2nd August 2016) - Kamba, S.; Simon, E.; Skoromets, V.; Bovtun, V.; Kempa, M.; Pokorný, J.; Savinov, M.; Koruza, J.; Malič, B.
ABSTRACT: Dielectric properties of 0.5Ba(Ti0.8 Zr0.2 )O3 –0.5(Ba0.7 Ca0.3 )TiO3 ceramics were probed in the frequency range from 10 Hz to 100 THz in a broad temperature range (10–900 K). Polar soft phonon observed in infrared spectra softens with cooling; however, below 500 K, its frequency becomes temperature independent. Simultaneously, a central mode activates in terahertz and microwave spectra; and it actually drives the ferroelectric phase transitions. Consequently, the phase transitions strongly resemble a crossover between the displacive and order–disorder type. The central mode vanishes below 200 K. The dielectric relaxation in the radiofrequency and microwave range anomalously broadens on cooling below T C1, resulting in the nearly frequency independent dielectric loss below 200 K. This broadening comes from a broad frequency distribution of ferroelectric domain wall vibrations. Raman spectra reveal new phonons below 400 K, i.e. already 15 K above T C1 . Several weak modes are detected in the paraelectric phase up to 500 K in Raman spectra. Activation of these modes is ascribed to the presence of polar nanoclusters in the material.